2020
DOI: 10.3390/ani10091681
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Culture Increases Omega-3 Long-Chain Polyunsaturated Fatty Acids (N-3 LC-PUFA) Levels in Japanese Sea Bass (Lateolabrax japonicus), Probably by Upregulating Elovl5

Abstract: The fatty acid compositions of the fish muscle and liver are substantially affected by rearing environment. However, the mechanisms underlying this effect have not been thoroughly described. In this study, we investigated the effects of different culture patterns, i.e., marine cage culture and freshwater pond culture, on long-chain polyunsaturated fatty acids (LC-PUFA) biosynthesis in an aquaculturally important fish, the Japanese sea bass (Lateolabrax japonicus). Fish were obtained from two commercial farms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
4
12
0
Order By: Relevance
“…Inspired by this, we compared myofibril diameter and density in the samples, and revealed that high salinity significantly decreased myofibril diameter, but significantly increased myofibril density. Combined with the finding in our previous studies that salinity (or marine cage culture as compared with freshwater pond culture) significantly affects fish crude body composition [ 5 , 26 ], we conclude here that ambient salinity may change fish flesh texture through comprehensive effects on muscle composition and myofibril structure.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Inspired by this, we compared myofibril diameter and density in the samples, and revealed that high salinity significantly decreased myofibril diameter, but significantly increased myofibril density. Combined with the finding in our previous studies that salinity (or marine cage culture as compared with freshwater pond culture) significantly affects fish crude body composition [ 5 , 26 ], we conclude here that ambient salinity may change fish flesh texture through comprehensive effects on muscle composition and myofibril structure.…”
Section: Resultssupporting
confidence: 86%
“…Shear value test revealed that salinity of 0.9% significantly decreased muscle tenderness compared with S 0 group ( p < 0.05, Table 1 ), which was consistent with the significantly decreased moisture content in 0.9% group in our previous study [ 26 ]. Similar results were also obtained in Japanese sea bass, in which marine cage culture led to a significant decrease in muscle moisture content and tenderness compared with freshwater pond culture [ 5 ]. Texture parameters, including hardness, chewiness, gumminess, and adhesiveness significantly increased with water salinity ( p < 0.05, Figure 1 ) while springiness decreased ( p < 0.05).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…However, studies testing Apelin in fish species are scarce. Experiments were conducted to test the effects of Pyr-apelin-13 (an active form of apelin) on common carp in vitro (hypothalamus) and in vivo [12]. The results in vitro and in vivo displayed an upregulation of appetite-and growth-related genes, such as growth hormone receptor (GHR) and insulin-like growth factors 1 and 2 (IGF1 and IGF2, respectively), supporting the hypothesis that this orexigenic peptide might regulate the feeding and growth of this important commercial species.…”
mentioning
confidence: 99%